Assessment of Natural Bentonite Efficacy for Dye Removal in Textile Wastewater Treatment : Implication for Mitigating River Citarum Pollution - Fathan Nabhani, az; Zahidah; Herawati, Heti; Zulti, Fifia (LIMNOTEK Perairan Darat Tropis di Indonesia, 2024)
Textile industries contribute significantly to the economy but release harmful pollutants into the environment, especially rivers.  The effluent from the textile industry contained toxic dyes that can harm the river ecosystem.  Several studies have been conducted to reduce toxic dyes in a river system using bentonite as an adsorbent to reduce river pollution effectively.  However, the effectiveness of bentonite still needs to be tested again using textile liquid waste that has not gone through any waste processing at all.  Citarum is one of the main rivers on Java Island, which suffers from textile effluent, especially azo dyes which are toxic, mutagenic and carcinogenic which can harm the aquatic ecosystem.  Therefore, this study aims to implement natural bentonite as an adsorbent to remove dyes from textile wastewater.  We performed a laboratory test to adsorption on bentonite and textile wastewater considering the variation of adsorbent weight of 10 g and 20 g in 100 mL of textile wastewater stirred in an Erlenmeyer flask at room temperature for 0-300 minutes.  The initial concentration of textile wastewater used was 10%, 30%, and 50%.  We found that the maximum dye removal efficiency was 91.25% with 10% initial concentration treatment, 20 g adsorbent weight, and 60 minutes contact time.  Longer contact time will increase the removal efficiency and adsorption capacity, while higher adsorbent dosage will decrease the concentration of dyes in wastewater.  Efficient textile wastewater treatment has improved water quality, effectively meeting river water quality standards and environmental regulations.